Examining the Effects of Remote Auditing, Technostress, and Digital Collaboration on Auditor Performance - Ricky Bryan D.P. Tampubolon (Jurnal Ekonomi dan Bisnis Digital, 2026)
The rapid adoption of digital technologies has transformed the way audit engagements are planned, executed, and coordinated, requiring auditors to adapt to increasingly technology-intensive work environments. This study examines the effects of remote auditing, technostress, and digital collaboration on auditor performance. A quantitative explanatory research design was employed, with data collected through questionnaires distributed to external auditors working at audit firms across Jakarta. The respondents were required to have a minimum of two years of professional experience as auditors, resulting in 50 usable responses. The data were analyzed using multiple linear regression after the measurement instruments and classical assumptions were assessed. The findings demonstrate that remote auditing has a positive and significant effect on auditor performance, indicating that technology-enabled audit arrangements can facilitate the execution of audit tasks and improve work effectiveness. Technostress also exhibits a positive and significant effect on auditor performance, contrary to the hypothesized negative relationship. This finding suggests that technology-related demands may function as challenge stressors that encourage auditors to adapt, develop technological competencies, and maintain their performance. Digital collaboration likewise has a positive and significant effect on auditor performance, highlighting the importance of technology-mediated communication, information sharing, and coordination within audit teams.